The psychology of the car : automobile admiration, attachment, and addiction - Gossling, Stefan (Elsevier, 2017)
The Psychology of the Car explores automotive cultures through the lens of psychology with the goal of achieving a low-carbon transport future. Worldwide there are now more than one billion cars, and their number grows continuously. Yet there is growing evidence that humanity needs to reach 'peak cars' as increased air pollution, noise, accidents, and climate change support a decline in car usage. While many governments agree, the car remains attractive, and endeavors to change transport systems have faced fierce resistance. Based on insights from a wide range of transport behaviors, The Psychology of the Car shows the "why#x94; of automotive cultures, providing new perspectives essential for understanding its attractiveness and for defining a more desirable transport future.